2017
DOI: 10.1021/acs.langmuir.7b00289
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Viscoelasticity of Peptide Vesicles by Adjusting Hydrophobic Helical Blocks Comprising Amphiphilic Polypeptides

Abstract: Amphiphilic block polypeptides of poly(sarcosine)-b-(l-Val-Aib) and poly(sarcosine)-b-(l-Leu-Aib) and their stereoisomers were self-assembled in water. Three kinds of binary systems of poly(sarcosine)-b-(l-Leu-Aib) with poly(sarcosine)-b-poly(d-Leu-Aib), poly(sarcosine)-b-poly(l-Val-Aib), or poly(sarcosine)-b-(d-Val-Aib) generated vesicles of ca. 200 nm diameter. The viscoelasticity of the vesicle membranes was evaluated by the nanoindentation method using AFM in water. The elasticity of the poly(sarcosine)-b-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…7 The precise control over PSar synthesis has enabled the accurate synthesis of block copolymers that contain PSar conjugated to other polypeptoids, [8][9][10] poly(ε-caprolactone), 11,12 tertiary aminecontaining molecules, 13 PEG, 14 and poly(amino acids)/polyamides. [15][16][17] There has been much recent interest in the application of PSar for the controlled release of therapeutic compounds. In such instances, PSar habitually forms the hydrophilic, and nonfouling, section of an amphiphilic block copolymer capable of forming nanoparticles in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…7 The precise control over PSar synthesis has enabled the accurate synthesis of block copolymers that contain PSar conjugated to other polypeptoids, [8][9][10] poly(ε-caprolactone), 11,12 tertiary aminecontaining molecules, 13 PEG, 14 and poly(amino acids)/polyamides. [15][16][17] There has been much recent interest in the application of PSar for the controlled release of therapeutic compounds. In such instances, PSar habitually forms the hydrophilic, and nonfouling, section of an amphiphilic block copolymer capable of forming nanoparticles in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…The amphiphilic polypeptides PSar 28 - b -( l -Leu-Aib) 6 (S28L12) and PSar 27 - b -( l -Leu-Aib) 8 (S27L16) were synthesized as reported previously [ 21 , 22 , 25 , 27 ]. The amphiphilic polypeptides PSar 24 - b -( l -Leu-Aib) 2 -( l -Ala-Aib) 2 -( l -Leu-Aib) 2 (S24L4A4L4) and PSar 26 - b -( l -Ala-Aib)-( l -Leu-Aib) 6 -( l -Ala-Aib) (S26A2L12A2) were synthesized by modifying a reported synthesis scheme [ 21 , 22 , 24 , 27 ] ( Schemes S1 and S2 ). Briefly, dipeptide units of Leu-Aib and Ala-Aib were synthesized with traditional condensation, and the 12 and 16 mer hydrophobic peptide was obtained by combining their units with sequential liquid-phase synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…The phenomenon was explained by the hypothesis that the helical part is uniformly packed in a hydrophobic layer due to the concave–convex interaction between helices with the LxxxLxxxL sequence [ 20 , 21 , 22 , 23 ]. Kimura and coworkers demonstrated that PSar n - b -( l -Val-Aib) 6 did not form a nanotube [ 24 ], which showed the importance of the Leu side chain for morphology control. Thus, although soft matter may spontaneously form from amphipathic molecules, its homogeneity and shape design are possible with the precise molecular orientation found in proteins.…”
Section: Introductionmentioning
confidence: 99%
“…23 Over the last years, studies on the synthesis and self-assembly behavior of PSar-based block copolymers for the development of nanostructures of biotechnological interest have been presented, although they involve the use of conventional self-assembly procedures in dilute aqueous solutions. 13,23,[27][28][29][30][31][32] Recently, polymerization-induced self-assembly (PISA) has been established as an efficient methodology for facile one-pot fabrication of polymeric nano-objects with predictable morphologies at high solids concentrations (10-50% w/w). [33][34][35][36] Existing limitations of traditional self-assembly strategies (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, studies on the synthesis and self-assembly behavior of PSar-based block copolymers for the development of nanostructures of biotechnological interest have been presented, although they involve the use of conventional self-assembly procedures in dilute aqueous solutions. ,, Recently, polymerization-induced self-assembly (PISA) has been established as an efficient methodology for facile one-pot fabrication of polymeric nano-objects with predictable morphologies at high solids concentrations (10–50% w/w). Existing limitations of traditional self-assembly strategies (i.e., direct dissolution, thin-film hydration, and solvent-switch) such as low polymer concentrations (≤1% w/w) and laborious post-polymerization processing steps for targeting certain morphologies are proven to be overcome by PISA. Only selected monomers have the ability to undergo PISA as a solubility transition of the gradually growing core-forming block from solvent-soluble to solvent-immiscible is required .…”
Section: Introductionmentioning
confidence: 99%